Sub-National Authoritarianism after the New Order: Relationship of Political Recruitment and Political Culture with Political Dynasties in Indonesia (Faculty of Social Science, Universitas Negeri Semarang, 2022)
The transition of the Indonesian government from a centralized to a decentralized one, marked by the granting of autonomy to the regions to manage their regions, raises political problems. One of the political problems is the emergence of political dynasties at the sub-national level. The emergence of political dynasties in regional elections at the sub-national level in Indonesia has experienced a significant increase. For this reason, this article will research the emergence of political dynasties in regional elections at the sub-national level in Indonesia. The method used in this research is the literature study method. A literature study is related to data collection methods that involve reviewing literature, reading and taking notes, and processing research materials. The results of this study indicate that, apart from weak regulations, another aspect that causes the emergence of political dynasties is the process of political recruitment by political parties that nominate candidates based on the capacity of candidates as regional heads. Nominations for regional heads by political parties are based on the local community's political culture, which wants to maintain the status quo. Political parties carry out unfair political recruitment to nominate candidates for regional heads so that they nominate candidates from political dynasties by using the image of their predecessors, which makes the emergence of political dynasties more and more common in Indonesia, especially at the sub-national level. Therefore, the recruitment of political parties to elect regional head candidates is highly dependent on the political culture of the local community. The link between society's political culture and political recruitment has led to the emergence of political dynasties at the sub-national level in Indonesia.